Investigação do potencial antimicrobiano de plantas do cerrado no controle de micro-organismos simbiótico da Diabrotica speciosa - Luiz, Anderson Luigi (2014)
In the cerrado biome it is estimated approximately 160.000 species of plants, animals and fungi that, through their history have been exposed to complex interactions. Those interactions have created a complex system of intra and inter-species chemical communication, constituting a fascinating and fertile area of scientific investigation. Thus, this project aimed to develop a multidisciplinary initiative. Forging chemical ecology, natural products chemistry and microbiology to a joint action for the understanding of plague insects microorganisms interactions. It also aims to investigate how the chemistry of natural products can interfere with this cycle proposing a new mechanism of action for controlling pest insects. Microbial diversity of Diabrotica speciosa was evaluated and as results it was obtained 56 microorganisms. Isolates were assembled into 12 different groups through statistical analysis of the respective MALDI TOF MS mass spectra. The microorganisms were identified to genus level, using the same technique, such as Serratia, Enterobacter, Acinetobacter, Stenotrophomonas, Sphingobacterium, Pseudomonas, Ochrobactrum and Streptomyces. The joint analysis of entomo-microbiological studies and the technique of MALDI TOF MS allowed to identify bacterial strains from vertical and horizontal transmissions. Extracts of 24 plant species collected in the cerrado were prepared and submitted to antimicrobial assays for verification of growth inhibition of isolated strains. The plant species that have shown best results were Anadenanthera falcata, Campomanesia pubescens and Psidium laruotteanum. In the phytochemistry study of P. laruotteanum extracts it was possible to isolate xvii two flavonoids and a chalcone, the latter was used as a reference marker for testing the quality control of the plant extract and fractions. The biological tests in D. speciosa showed that extract of P. laruotteanum altered insect s development. Thus the purpose of the study was achieved, since it can be concluded that the control of symbiotic microorganisms can interfere with the insect survival, and thus propose a new form of biorational pest control insects.